Health attacks and protection strategies during Gaza's Great March of Return: a mixed methods study using data from WHO's Surveillance System for Attacks on Healthcare. (July 2021) - Shehada, Walaa; Bouquet, Benjamin; Nassar, Juliana; Briody, Carolyn; Alfarra, Nadia; Doctor, Henry V; Daher, Mahmoud; Rockenschaub, Gerald; Kirkwood, Graham; Pollock, Allyson; Kim, Hyo-Jeong
Abstract: Background: WHO defines an attack on health care as "any act of verbal or physical violence or obstruction or threat of violence that interferes with the availability, access and delivery of curative and/or preventive health services during emergencies." Gaza's Great March of Return (GMR) began on Mar 30, 2018, with 322 Palestinians killed and 33 141 injured by December, 2019, and first-response health-care teams exposed to high levels of violence. The aims of this study were threefold: to explore the vulnerabilities of health workers to attacks during the GMR; to understand the effectiveness and comprehensiveness of systems for monitoring health attacks; and to identify potential strategies and interventions to improve protection. Methods: WHO's Surveillance System for Attacks on Healthcare (SSA) verifies and records health attacks. We analysed SSA data for the Gaza Strip from Mar 30, 2018, to Dec 31, 2019, examining the number and type of attacks, the mechanisms of injury, and the distribution of attacks by gender, time, and location. We analysed the correlation of health worker injuries and deaths with total injuries and deaths of Palestinians during the GMR. We held interviews and focus groups with individuals working for organizations defined as partners contributing to the SSA in the Gaza Strip, to understand data comprehensiveness, the nature and impact of violence, and protection gaps and strategies. Findings: During the study period, there were 567 confirmed incidents, in which three health workers were killed, 845 health workers were injured, and 129 ambulances and vehicles and 7 health facilities were damaged, including one hospital and three medical field stations. Of the total health personnel killed and injured, 166 of 848 (20%) were in the Gaza governorate, 274 (32%) were in the Khan Yunis governorate, 119 (14%) were in the middle governorate, 192 (22%) were in North governorate, and 96 (11%) were in the Rafah governorate. Of 845 injuries, 743 (88%) were in men, 45 (5%) were live ammunition injuries, 62 (7%) were rubber bullet injuries, 151 (18%) were gas canister injuries, 41 (5%) were shrapnel injuries, and 533 (64%) were gas inhalation injuries. Injuries and deaths among health workers correlated moderately (R2=0·54) with and accounted for 2% of the total. Qualitative findings highlighted the incidental and structural nature of violence, normalisation and under-reporting of attacks, the need for improved coordination of protection for health care, and gaps in the availability of protective equipment. Interpretation: Health-care workers function at great personal risk. The correlation of attacks against health care with total injuries and deaths points to the need for alignment of efforts to protect health care with strategies to safeguard civilian populations, including protection of populations living under occupation and those engaged in civil demonstrations. Health-care workers identified the need for systemic measures to improve protection through training, monitoring, and coordination, and through linking of monitoring and documentation of health attacks with stronger accountability measures for prevention. Funding: In 2017 and 2018, WHO's Right to Health Advocacy programme received funding from the Swiss Development Cooperation and the oPt Humanitarian Fund.